2018
DOI: 10.1127/ejm/2018/0030-2753
|View full text |Cite
|
Sign up to set email alerts
|

Spanish palygorskites: geological setting, mineralogical, textural and crystal-chemical characterization

Abstract: A representative group of palygorskites from the six most important Spanish deposits and six other occurrences were studied comparing their mineralogy, textural features, crystal-chemistry, and surface properties. These palygorskites have different geological origin: (1) sedimentary in large Tertiary continental basins, (2) hydrothermally altered volcanic rocks in the southern Spanish Peninsula, also Tertiary in age; and (3) fault-hosted pure palygorskites. The most common impurities are quartz and carbonates,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 63 publications
2
1
0
Order By: Relevance
“…X-ray diffraction (XRD) patterns of the raw and acid-treated (2, 4, and 6 mol/L) Brazilian palygorskite are illustrated in Figure 1. Palygorskite (ICCD 21-0958) and quartz (ICCD 46-1045) phases were identified in the raw and acid-activated clays, as observed in other studies [58][59][60]. Câmara et al and Suarez et al [39,58] reported that the palygorskite can be classified into three types: Type I has similar Al and Mg contents and negligible isomorphic substitutions (d200 < 6.35 Å); Type II is rich in Al contents and has a dioctahedral character, and this is the most commonly found type (6.35 < d200 < 6.46 Å); and Type III is rich in Mg contents and has a trioctahedral character (d200 > 6.46 Å).…”
Section: Regeneration Of Adsorbentssupporting
confidence: 79%
“…X-ray diffraction (XRD) patterns of the raw and acid-treated (2, 4, and 6 mol/L) Brazilian palygorskite are illustrated in Figure 1. Palygorskite (ICCD 21-0958) and quartz (ICCD 46-1045) phases were identified in the raw and acid-activated clays, as observed in other studies [58][59][60]. Câmara et al and Suarez et al [39,58] reported that the palygorskite can be classified into three types: Type I has similar Al and Mg contents and negligible isomorphic substitutions (d200 < 6.35 Å); Type II is rich in Al contents and has a dioctahedral character, and this is the most commonly found type (6.35 < d200 < 6.46 Å); and Type III is rich in Mg contents and has a trioctahedral character (d200 > 6.46 Å).…”
Section: Regeneration Of Adsorbentssupporting
confidence: 79%
“…Moreover, their macroscopic similarities undeniable. The crystals shown in Figure 5 occur as thin, elongated fibers of varying lengths, r domly distributed in different ways: isolated, grouped in a few units parallel to each ot or forming massive bundles from the agglomerated structures [65,66]. Pharmasorb ® loidal fibers were shorter than in the raw palygorskite, which corroborates the data sho in Table 2.…”
Section: Electron Microscopy Analysissupporting
confidence: 78%
“…The contact angle results for the investigated materials are shown in Figure 10. The contact angle, in addition to enabling the assessment of the hydrophilicity or hydrophobicity of a material [38,58,59], also allows the assessment of surface energy [60], which is an important parameter during the production of compatible bioblends. Figure 10 shows the acquired data for the contact angle, where PLA displayed a value of 63 .…”
Section: Contact Anglementioning
confidence: 99%